2021
DOI: 10.1186/s12877-021-02536-9
|View full text |Cite
|
Sign up to set email alerts
|

Higher prevalence of geriatric depression, catastrophizing pain and sleep disorders in institutionalized elders: a cross-sectional study in Galle District, Sri Lanka

Abstract: Background Population aging is a significant social problem in the twenty first century. Recent economic and social changes lead increasing number of elders to spend their lives in elderly homes. Institutionalized elders have to face many physical and psychological problems which negatively impact their quality of life. Geriatric depression (GD), catastrophizing pain (CP) and sleep disorders (SD) are some common problems among them. Methods Present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Excessive use of opioid analgesics by some pain patients may disrupt the balance between protein degradation and synthesis, leading to and exacerbating the progression of sarcopenia ( 48 ). Clinical studies have shown that chronic pain is often accompanied by comorbidities such as anxiety, depression, and sleep disorders ( 49 ), and those comorbidities are associated with an increased risk of developing sarcopenia ( 50 , 51 ). Overall, by gaining a deeper understanding of the relationship and the underlying mechanisms between the two, it will be beneficial for physicians and patients to recognize the importance of comprehensive screening for pain and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive use of opioid analgesics by some pain patients may disrupt the balance between protein degradation and synthesis, leading to and exacerbating the progression of sarcopenia ( 48 ). Clinical studies have shown that chronic pain is often accompanied by comorbidities such as anxiety, depression, and sleep disorders ( 49 ), and those comorbidities are associated with an increased risk of developing sarcopenia ( 50 , 51 ). Overall, by gaining a deeper understanding of the relationship and the underlying mechanisms between the two, it will be beneficial for physicians and patients to recognize the importance of comprehensive screening for pain and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…In Galle district, the prevalence was 34.3% in 2019 [ 21 ]. Higher prevalence of depression [ 4 ], limitations to social and physical activities [ 8 ], poor quality of life [ 6 ] and under nutrition [ 22 ] among institutionalized older adults could be a few reasons for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the elderly population in a country, it can be mainly subdivided as; community dwelling older adults and, institutionalized older adults. The recent changes in the economy as well as the society have paved the way for an increasing proportion of older adults spending their lives in elderly care institutions [ 4 ]. It was only 1% of the total elderly population in Sri Lanka that was institutionalized in 2012 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as per a study conducted in the Galte district of Sri Lanka, the prevalence of inadequate sleep quality among the elderly was 55.5%. Also, males had a lower prevalence rate of (37.8%) compared to females (62.2%) (Abeysekera & De Zoysa, 2021). As indicated by a research study conducted in the city of Dhaka, Bangladesh, 72% of the elderly population had a sleep disorder, 71% had reported insomnia ,2% had sleep apnea, 18% had psychiatric disorder, and 13% had movement disorder (Hossen, 2022).…”
Section: Introductionmentioning
confidence: 95%